Expediente e nominata - Redação, REVER (REVER: Revista de Estudos da Religião, 2020)
Avaliadores desta edição Alexandre Palma (UCP); Alzirinha Rocha de Souza (UNICAP); Camila Cabral Arêas (UCP); Cândido Moreira Rodrigues (UFMT); Caio C. Boschi (PUC-Minas); Ceci M. Costa Baptista Mariani (PUC-Minas); Clara Saraiva (ULisboa); David Junior de Souza Silva (UNIFAP); Dilaine Soares Sampaio (UFPB); Donizete Rodrigues (UBI); Edile Maria Fracaro Rodrigues (PUC-PR); Fernanda Cravidão (UC); Giulia Cavallo (IUL); João Marques Eleutério (UCP); José Brissos-Lino (ULusófona); Kátia Marly Leite Mendonça (UFPA/UEPA); Luís M. Figueiredo Rodrigues (UCP); Magali do Nascimento Cunha (autônoma); Margarida M. F. H. C. M. da Franca (UC); Marcos Vinicius da Costa Meireles (IFRO); Maria da Graça Poças Santos (IPLeiria); Maria Isabel Pereira Varanda (UCP); Miguel Assis Raimundo (ULisboa); Newton Darwin de Andrade Cabral (UNICAP); João Luís Jesus Fernandes (UC); João Manuel Duque (UCP); Joaquim Costa (UMinho); Jorge Botelho Moniz (UNL); José Nunes (UCP); José Pereira Coutinho (UCP); Rita Mendonça Leite (UCP); Rodrigo Portella (UFJF); Saulo de Tarso Cerqueira Baptista (UEPA); Steffen Dix (UCP); Taciana Brasil dos Santos (autônoma); Teresa Líbano Monteiro (ULisboa); Teresa M. Leal de Assunção M. Toldy (UFP); Valéria Rocha Torres (autônoma); Vinicius Saragiotto Magalhães do Valle (FASM); Waldney de Souza Rodrigues Costa (UERN); Zuleica Dantas (UNICAP)